(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present research paper compares the indexing and query optimization techniques in respect to their influence on the functioning of relational databases. An important method is indexing and optimization of queries to enhance the efficiency and speed of information retrieval. The paper employs such practical evaluation on a given sample data and it compares a range of indexing techniques approaches (e.g. the B-tree, hash index), as well as optimization strategies (e.g. cost-based, heuristic-based). The descriptive statistics and hypothesis testing is used in analyzing. The outcomes give information on which methods can work better in a particular scenario, on how database developers and administrators can be advised.